A Single Dose of Joint in tne Treatment of Soil-ranmitted Helminthic Infections With Special Emphasis on Hookworm Infection - Noerhajati S, Noerhajati S (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1975)
Phendyne-diisothiocyanate 1.4. (JONIT) or Bitoscanate in a single, doseof 150 mg was given to 34 patients infected with hookworm. Besides habit-worm, they also harboured the common species of soil-transmitted helminths, such as Ascaris lumbricoides and Trichuris trichiura.The result of the study .shoWed-flat the drug was effective against hookworm and less effective against A. lumbricoides and T. trichiura infections. The cure rates were 82.35%, 47.05% and 26.47 % for hookworm, A. lumbri-: coides and T. trichiura respectively.The side effects, including nausea, vomiting, diarrhoea,. giddiness orheadache and abdominal discomfort were mild and transient which did not require any treatment.